The status quo of information management in hospitals: results of an online survey - Kücherer, Christian; Paech, Barbara (Informatik 2016 - Tagung vom 26.-30. September 2016 in Klagenfurt, 2016)
Information Management (IM) departments in hospitals provide IT services supporting patient care and administrative hospital functions. Complexity and impacts of IT failures are continuously increasing. Therefore, professional IM departments are necessary, even though their importance is commonly underestimated.